Kontribusi Informasi, Fasilitas, dan Loyalitas User Dalam Menggunakan Aplikasi Fintech di Masa Pandemi Covid-19 - Rendika Vhalery (Sosio e-Kons, 2021)
Covid-19 is still a hot issue in Indonesia that causes some changes such as in finance either buying or paying through fintech.  In this study we aimed to find out if there is an influence of information, facilities, and loyalty in using fintech applications in the covid-19 pandemic? . The research method used is quantitative with any type of associative research. The research population is a student of the economic education study program of Indraprasta University PGRI Jakarta. A study sample of 150 students. Data collection techniques using questionnaires. Data collection techniques use the help of google form website to make it easier to collect data due to the current lockdown situation. Data analysis techniques use multiple linear regressions. The results revealed that (1)  there is an influence of information in using fintech applications during the covid-19 pandemic, (2) there is the influence of facilities in using fintech applications during the covid-19 pandemic, (3) there is a loyalty influence in using fintech applications during the covid-19 pandemic, and (4) there is the influence of information, facilities, and loyalty in using fintech applications during the covid-19 pandemic.  The contribution of variable information, facilities, and  user loyalty in using fintech  applications during the covid-19 pandemic amounted to 0.471 or 47.1%.  Of the three variables that affect the use of fintechapplications, loyalty variables contribute the most.